Estrogen-Cholinergic Interactions: Implications for Cognitive Aging - Newhouse, Paul (Horm Behav, 2015)
While many studies in humans have investigated the effects of estrogen and hormone therapy on cognition, potential neurobiological correlates of these effects have been less well studied. An important site of action for estrogen in the brain is the cholinergic system. Several decades of research support the critical role of CNS cholinergic systems in cognition in humans, particularly in learning and memory formation and attention. In humans, the cholinergic system has been implicated in many aspects of cognition including the partitioning of attentional resources, working memory, inhibition of irrelevant information, and improved performance on effort-demanding tasks. Studies support the hypothesis that estradiol helps to maintain aspects of attention and verbal and visual memory. Such cognitive domains are exactly those modulated by cholinergic systems and extensive basic and preclinical work over the past several decades has clearly shown that basal forebrain cholinergic systems are dependent on estradiol support for adequate functioning. This paper will review recent human studies from our laboratories and others that have extended preclinical research examining estrogen-cholinergic interactions to humans. Studies examined include estradiol and cholinergic antagonist reversal studies in normal older women, examinations of the neural representations of estrogen-cholinergic interactions using functional brain imaging, and studies of the ability of selective estrogen receptor modulators such as tamoxifen to interact with cholinergic-mediated cognitive performance. We also discuss the implications of these studies for the underlying hypotheses of cholinergic-estrogen interactions and cognitive aging, and indications for prophylactic and therapeutic potential that may exploit these effects.